2011
DOI: 10.1111/j.1438-8677.2010.00374.x
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient virus resistance mediated by artificial microRNAs that target the suppressor of PVX and PVY in plants

Abstract: MicroRNAs (miRNAs) processed from nuclear-encoded transcripts control expression of target transcripts by directing cleavage or translational inhibition. Artificial miRNAs (amiRNAs) that exploit this endogenous gene silencing mechanism can be designed to target any gene of interest and provide a highly specific approach for effective post-transcriptional gene silencing (PTGS) in plants. Here, using Arabidopsis thaliana miR159a, miR167b and miR171a precursors as backbones, we designed two types of amiRNA target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
56
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(57 citation statements)
references
References 45 publications
0
56
0
1
Order By: Relevance
“…Furthermore, co-expression of two amiRNA precursors on the same construct to generate a dimeric amiRNA could be used to produce two amiRNAs and provide resistance to two different viruses (Niu et al 2006). Another study has also reported that transgenic N. tabacum expressing amiRNAs targeting HC-Pro and p25 from A. thaliana pre-miR159a showed highly specific resistance against PVY and PVX (Ai et al 2011). Therefore, chimeric hpRNA, shRNA, and multimeric amiRNA strategies are all extremely useful to address the issue of multiple virus infections under field condition.…”
Section: Multiple Virusesmentioning
confidence: 93%
See 2 more Smart Citations
“…Furthermore, co-expression of two amiRNA precursors on the same construct to generate a dimeric amiRNA could be used to produce two amiRNAs and provide resistance to two different viruses (Niu et al 2006). Another study has also reported that transgenic N. tabacum expressing amiRNAs targeting HC-Pro and p25 from A. thaliana pre-miR159a showed highly specific resistance against PVY and PVX (Ai et al 2011). Therefore, chimeric hpRNA, shRNA, and multimeric amiRNA strategies are all extremely useful to address the issue of multiple virus infections under field condition.…”
Section: Multiple Virusesmentioning
confidence: 93%
“…The miRNA precursor backbones that are highly expressed in organisms are the best for amiRNA function. By comparison of the three different amiRNA-mediated resistances, the different resistance levels of transgenic plants were positively correlated with the expression levels of amiRNAs (Ai et al 2011). Concerning the study of targeting viral sequence, targeting 2a and 2b RNAs of CMV induced a higher antiviral ability than only targeting 2b (Qu et al 2007;Zhang et al 2011a).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…The amiRNA based approach for antiviral resistance was first demonstrated by targeting virus silencing suppressor P69 and HC-Pro of turnip yellow mosaic virus and turnip mosaic virus, respectively, in Arabidopsis [19]. Additional examples of antiviral resistance using the amiRNA-based approach to target different viral genes including 2b gene, 3’ untranslated region (UTR), coat protein (CP), nuclear inclusion protein a and b, and silencing suppressors have been documented for cucumber mosaic virus (CMV), potato virus X (PVX), and potato virus Y (PVY) [20,21,22,23]. More recently, improved plant resistance was achieved by targeting the nucleoprotein (N) but not silencing suppressor genes (NSs) in tomato spotted wilt virus (TSWV) using a shortened miR159a precursor backbone [24].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed several studies demonstrated that artificial miRNAs (amiRNAs) targeting key components of the viral replication machinery can efficiently impair viral growth upon infection [59][60][61][62][63][64][65]. These efforts have revealed that such resistance is cell-autonomous, inheritable, more efficient than siRNA-mediated strategies and successful in blocking viral replication and movement [59,66].…”
Section: Sncrnas and Viruses: New Frontiers Of Defensementioning
confidence: 99%